2010
DOI: 10.1371/journal.pone.0013711
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of VIA, Pap, and HPV DNA Testing in a Cervical Cancer Screening Program in a Peri-Urban Community in Andhra Pradesh, India

Abstract: BackgroundWhile many studies have compared the efficacy of Pap cytology, visual inspection with acetic acid (VIA) and human papillomavirus (HPV) DNA assays for the detection cervical intraepithelial neoplasia and cancer, few have evaluated the program effectiveness.Methods and FindingsA population-based sample of 5603 women from Medchal Mandal in Andhra Pradesh, India were invited to participate in a study comparing Pap cytology, VIA, and HPV DNA screening for the detection of CIN3+. Participation in primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
144
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 41 publications
5
144
1
2
Order By: Relevance
“…A population-based study conducted in rural India where VIA providers were gynecologists with renowned experience who rigorously followed the JHPIEGO Cervical Cancer Prevention Guidelines for Low-Resource Settings competency-based training tool 35 and who were quality assessed on a yearly basis during the study period, showed a sensitivity of VIA for detecting CIN21 of 26.3%. 36 In a more recent study of 4,656 women in India where screening was performed by well-trained nurses with regular retraining and quality control, sensitivity of VIA to detect CIN2 1 was 21.9%. 37 Another study conducted in United States some years ago where training and monitoring of test providers should have been optimal, found sensitivity of VIA for CIN21 to be 29%.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study conducted in rural India where VIA providers were gynecologists with renowned experience who rigorously followed the JHPIEGO Cervical Cancer Prevention Guidelines for Low-Resource Settings competency-based training tool 35 and who were quality assessed on a yearly basis during the study period, showed a sensitivity of VIA for detecting CIN21 of 26.3%. 36 In a more recent study of 4,656 women in India where screening was performed by well-trained nurses with regular retraining and quality control, sensitivity of VIA to detect CIN2 1 was 21.9%. 37 Another study conducted in United States some years ago where training and monitoring of test providers should have been optimal, found sensitivity of VIA for CIN21 to be 29%.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, 14 studies have been conducted in India to evaluate the accuracy and effectiveness of cervical cancer screening [23][24][25][26][27][28][29][30][31][32][33][34]. Studies have compared the specificity and sensitivity of visual inspection with acetic acid (VIA) or Lugol's iodine (VILI) and the Papanicolaou test and HPV DNA testing.…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
“…These approaches have been implemented by health workers such as auxiliary nurse midwives ( Table 2). The majority of these studies were cross-sectional in design and involved either community-or hospital-based samples [23][24][25][26][27][28][29][30][31][32]35]; two studies were randomized controlled trials [33, 36 -38]. To determine test sensitivity and specificity, most studies performed colposcopy for all participants and biopsy of abnormalities if indicated; in some, the colposcopist was blinded to the initial screening test results [24,26,27].…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may not be feasible for all women to receive regular Pap smears throughout their lives. Moreover, although the Pap smear is inexpensive, it is less accurate than the HPV-DNA test; therefore, screening at wider intervals with the highlysensitive HPV-DNA test may be more cost-effective than the current system (Gravitt et al, 2010;Levin et al, 2010;Chen et al, 2011;Flores et al, 2011;Shi et al, 2011). While HPV-DNA tests are not covered under the current NCSP, previous studies comparing screening methods have reported that the sensitivity of the Pap smear was improved markedly in combination with the HPV-DNA test (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%